Heating Rate Control in Electric Furnace with SSR and K-Type Thermocouple Using Arduino Uno Atmega 328P - Bayu Ega Pratama; Gurum Ahmad Pauzi; Sri Wahyu Suciyati; Amir Supriyanto (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Electric furnace is a tool that can be used to melt, heat, and change the physical shape of a substance. Electric furnaces sold in the market are still relatively expensive, therefore it is necessary to make an electric furnace at a low cost. This research designed an electric furnace using a K-type thermocouple sensor as a temperature reader and SSR relay as an ON/OFF heater control . Keypad serves to enter the temperature value in the heating furnace. The heating element used is 1 mm in diameter and 1.86 ohm resistance with a load of 21 Ampere, capable of heating a C1 type refractory brick furnace that has been tested to a temperature of 1000 OC. The results of temperature reading sensitivity tests against the type-K thermocouple sensor get a coefficient value of 0.99893, this indicates that the thermocouple sensor is worth using. From the electric furnace test thermocouple sensor has an average accuracy rate of 92.07%, as well as errors worth 7.93%. While there is a precision value of 98.786% which shows the system works optimally.